Comparative pharmacokinetics of tacrolimus in de novo pediatric transplant recipients randomized to receive immediate- or prolonged-release tacrolimus - Vondrak, Karel; Dhawan, Anil; Parisi, Francesco; Grenda, Ryszard; Debray, Dominique; Marks, Stephen D; Webb, Nicholas J A; Lachaux, Alain; Kazeem, Gbenga; Undre, Nasrullah (Pediatric transplantation, 2018)
Phase 2, parallel-group, multicenter, open-label, 4-week study, comparing PK of PR-T vs IR-T in de novo pediatric patients undergoing primary kidney, liver, or heart transplantation. Patients randomized 1:1 to receive once daily, PR-T-, or twice-daily, IR-T-based regimens; dose adjustments permitted after Day 1. Twenty-four-hour PK profiles collected on Days 1, 7, and 28. Primary endpoint: tacrolimus AUC24 . Secondary end points included tacrolimus C24 and Cmax . Endpoints compared between PR-T and IR-T on Days 1, 7, and 28. Predefined similarity interval for CIs of LSM ratios: 80%-125%. PK analysis set comprised 33 patients (PR-T, n = 15; IR-T, n = 18). Overall, AUC24 and Cmax were lower on Day 1 vs 7 and 28. Geometric LSM ratios of PR-T:IR-T on Days 1, 7, and 28 were 66.3%, 92.5%, 99.9%, respectively, for AUC24 ; 66.3%, 82.2%, 90.9% for C24 ; and 77.3%, 120.3%, 92.2% for Cmax . AUC24 90% CI within predefined similarity interval on Day 28; other 90% CIs fell outside. Linear relationship was similar between AUC24 and C24 , and between tacrolimus formulations, suggesting that the same therapeutic drug monitoring method can be used with both formulations in de novo pediatric allograft recipients.
Keywords: takrolimus; Heart Transplantation; Male; Child, Preschool; tacrolimus; Adolescent; Infant; Child; dítě; alografty; mužské pohlaví; Pediatrics; lineární modely; pediatrics; heart transplantation; transplantace srdce; mladiství; Tacrolimus; plocha pod křivkou; předškolní dítě; lidé; ženské pohlaví; Delayed-Action Preparations; Kidney Transplantation; transplantace ledvin; Humans; léky s prodlouženým účinkem; liver transplantation; pharmacokinetics; transplantace jater; Area Under Curve; kojenec; Linear Models; Liver Transplantation; Allografts; kidney transplantation; pediatrie; Female